Modul Peserta Didik Berbasis Pendekatan Matematika Realistik Kelas IV Sekolah Dasar - Yuliani, Refi Elfira; Heru, Heru; Wahidati, Wahidati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2021)
This study aims to produce a teaching material in the form of student modules based on PMRI approaches for grade IV elementary schools. The research method used is development research using the 4-D model (define, design, develop, disseminate). Subjects in the study were grade four students of SD IT Salsabila Palembang. Based on the research results obtained a valid and practical module. Validity can be from the results of the assessment of material experts, media modules and languages. Practicality can be from the results of the assessment of students in the field test is limited to the mathematical modules students developed. Based on data from the questionnaire analysis of students at the stage of limited field test, a score of 313 obtained from a maximum total of 352 assessments, which presented to be 88.92% and it could be categorized that the module developed practically. The potential effect was seen from the results of the student's final ability test. From the results of data analysis that has done that the average final score of students is 80.88 which means that the learning outcomes of students classified as an outstanding category, it can be concluded that the student mathematics module based on the PMRI approach that has developed as a potential effect on student learning outcomes students.